The Tradition of Weighing The Prospective Bride and Groom in The Wedding Customs of The Sekernan Muaro Jambi Community and Its Relevance in History Learning - Oktaria, Rahmi; Wahyuni, Anny (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
Learning about traditions is of course important so as not to lose existing culture and to be able to maintain and introduce wider traditions. This research aims to examine the tradition of weighing the bride and groom in the marriage customs of the Sekernan Muaro Jambi community and its relevance in learning history. This research uses qualitative research methods with a descriptive approach. Based on this research, it can be seen that the tradition of weighing the bride is a tradition passed down from generation to generation and is very closely related to the social life of the community and there are local wisdom values ​​in each implementation. It can be seen that the tradition of weighing the bride is a tradition passed down from generation to generation and is very closely related to the social life of the community.